EVALUATION OF THE EFFECTIVENESS OF THE SALES ACCOUNTING SYSTEM IN SUPPORTING THE SALES PROCESS AT PT PANCA TEHNIK - Amalia, Wia Rizqi; Nurhaliza, Widya (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
Facing intense competition in the service industry, PT. Panca Tehnik Banjarmasin must take advantage of developments in information technology to optimize the sales accounting system. The use of a computer-based accounting system that is integrated with inventory, payment and customer tracking systems can increase efficiency, accuracy and quality of sales services. This system also helps track sales performance and make strategic decisions to face competition. Based on field observations and interviews with a number of related staff, the results of this research indicate that there are weaknesses in PT's sales accounting system. Five Techniques, namely delays in data processing, obstacles in collecting account receivables, no credit limit control, and no database for document storage. The advantages of PT. Panca Tehnik in its sales accounting system is that there is a clear separation of duties, complete and documented archives and documents, and has developed several sales sub-systems that help forecast future sales activities.